2019
DOI: 10.1038/s41598-018-38334-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization and comparative studies of four Cecropia species collected in Panama using multivariate data analysis

Abstract: Plant species of the genus Cecropia (Urticaceae) are used as traditional medicine in Latin-America, and are commercially available as food supplements. The aim of this study was to characterize and compare the phytochemical constituents of four Cecropia species collected in Panama. The structures of 11 compounds isolated from leaves of C. obtusifolia were elucidated based on high resolution mass spectrometry (HRMS) and nuclear magnetic resonance (NMR) spectroscopic analysis; the polyphenolic constituents of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 62 publications
4
40
1
Order By: Relevance
“…In fact, a similar behavior described for most flavone di-C,O-glycosides in this research was observed. On the other hand, the intensity of the isovitexin peak (14) increased during the experiment (Fig. 3S, Supporting Information).…”
Section: Original Papersmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, a similar behavior described for most flavone di-C,O-glycosides in this research was observed. On the other hand, the intensity of the isovitexin peak (14) increased during the experiment (Fig. 3S, Supporting Information).…”
Section: Original Papersmentioning
confidence: 95%
“…For that reason, it is of great importance to conduct investigations on the biotransformation of flavonoid glycosides in the human body in order to provide further understanding of their beneficial impact on health [17]. As a first step toward the elucidation of the behavior of the crude extract of the leaves of C. obtusifolia, which are rich in flavone C-glycosides [14], the stability after oral ingestion in gastrointestinal conditions and colonic biotransformation was investigated. This is the first time that the biotransformation of the extract of C. obtusifolia, an important source of compounds known for their health-promoting effects, has been addressed under gastrointestinal conditions.…”
mentioning
confidence: 99%
“…One of the major concerns prior to the use of Dipterocarpus alatus is the age estimation as only the trees aged 25 years and above are usable. Despite several previous studies reporting a wide spectrum of phytochemicals obtained from different parts of Dipterocarpus alatus for pharmaceutical uses [10], there is, so far, no such reports exhibiting the age-or growth-associated metabolites of Dipterocarpus alatus. The current scientific method commonly used for age estimation is a physical method employing the calculation of the trunk diameter with growth factors and annual ring drilling [11].…”
Section: Introductionmentioning
confidence: 98%
“…Infusions of leaves, branches, bark, and roots are used for their hypoglycemic and hypolipidemic properties demonstrated in experimental animal and human models, both at a cellular and physiological level, which are attributed to chlorogenic acid (CGA), making C. obtusifolia a model plant for its potential use in the control of DM-2 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In the same way, it is known that C. obtusifolia is capable of synthesizing, in addition to CGA, other compounds of phenolic origin such as orientine, isoorientine, vitexin, isovitexin, caffeic acid, ferulic acid, quinic acid, quercetin, apigenin, luteolin, tormentoside, triterpenoid isomers of saponin-O-hexoside and chlorogenic acid, among others, which are known to be present in the leaves of the plant [ 15 , 16 , 17 ]. Studies on C. obtusifolia cell cultures have shown that nitrate starvation increases CGA production [ 18 ].…”
Section: Introductionmentioning
confidence: 99%